1973
DOI: 10.1111/j.1600-0609.1973.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin H Disease in a Turkish Family

Abstract: Hb H disease was found in a Turkish woman, her mother and two of her siblings. Although all had mild pallor and two had mild splenomegaly, these persons were asymptomatic. In addition to two anodal bands, interpreted as Hb H and Hb Bart's, a third band was seen on Hb‐starch‐gel electrophoresis at pH 7. The slightly elevated plasma Hb level, the presence of methaemalbumin, and the absence of haptoglobin in the serum of the propositus were attributed to haemolytic anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…We detected 198 patients with HbH disease when we searched articles from PubMed related to Turkish patients with HbH disease [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. When the results of our study were added to that number, we found 471 HbH cases to date from Turkey, and this number is fairly high ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We detected 198 patients with HbH disease when we searched articles from PubMed related to Turkish patients with HbH disease [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. When the results of our study were added to that number, we found 471 HbH cases to date from Turkey, and this number is fairly high ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%